The Role of Influencers in Promoting Transparency and Public Participation in Flood Management Through The #Wargabantuwarga Hashtag Movement - Ayu GiswantI, Wina; Burchanuddin, Burchanuddin; Anas, Ali (Jurnal Indonesia Sosial Sains, 2025)
Flood disasters constitute a major public issue that requires rapid, transparent, and participatory responses. The development of social media has introduced new actors in disaster governance, one of which is digital influencers who function as information intermediaries between the government and the public. This study aims to analyze the role of influencers in promoting transparency and public perspective in flood management through the hashtag movement #WargaBantuWarga from a public administration. This research employs a qualitative approach with a case study design. Data were collected through social media observation, interviews, and documentation. The findings indicate that influencers play a significant role in accelerating the dissemination of disaster-related information, enhancing transparency in aid distribution, and mobilizing public participation in the form of donations, volunteerism, and public oversight. The #WargaBantuWarga movement has proven to be an effective medium for collaboration among communities, influencers, and the government in flood response. This study concludes that influencers serve as strategic non-state actors in strengthening the principles of transparency and public participation in disaster governance in the digital era.